The Influence Of Transformational Leadership Style On Employee Performance At Bank Bri Soppeng Branch - Nurmilasari Nurmilasari; Amirah Amirah; Amni Sahra Awalya; Asmini Asmini (GENTARA: management and accounting research, 2026)
This study aims to analyze the influence of transformational leadership style on employee performance at Bank BRI Soppeng Branch. The main problem underlying this research is the phenomenon of low work motivation, lack of initiative, and weak interdepartmental coordination, which have an impact on the achievement of work targets. The research method used is associative quantitative research, with data collection techniques through questionnaires and documentation. The population of this study consisted of 45 employees, all of whom were used as samples through a total sampling (census) technique. Data were analyzed using simple linear regression with the assistance of SPSS software. The results show that transformational leadership style has a positive and significant effect on employee performance, with a significance value of 0.003 < 0.05 and a regression coefficient of 0.716. This indicates that the better the implementation of leadership characteristics such as charisma, inspirational motivation, intellectual stimulation, and individualized consideration, the higher the employee performance. This study suggests that management should continue to enhance individual support and guidance to optimize organizational productivity